Diversity of Salacca zalacca (Gaertn.) Voss from Bali, Indonesia based on morphological and molecular characters - I KETUT SUMANTRA; LISTIHANI LISTIHANI; PUTU EKA PASMIDI ARIATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sumantra IK, Listihani L, Ariati PEP. 2024. Diversity of Salacca zalacca (Gaertn.) Voss from Bali, Indonesia based on morphological and molecular characters. Biodiversitas 25: 1771-1780. There are several salak (Salacca zalacca (Gaertn.) Voss) variations based on epicarp (skin) color, pulp aroma, and taste. The different characters are not only found among different production centers, but also among plants cultivated in the same area. This study aimed to identify the morphological and molecular characters of 16 salak cultivars from Bali, Indonesia. Morphological characters were described based on the individual test guideline for salak species and molecular characters were analyzed using four Random Amplified Polymorphic DNA (RAPD) primers, namely OPA3, OPC7, OPD4, and OPD20. The morphological characters of 16 salak cultivars are very diverse in plant height, number of leaflets, leaflets length and width, leaf sheath length, fruit skin color, fruit shape, fruit length, fruit diameter, number of fruits per bunch, number of seeds per fruit, and thick pulp. A total of 37 DNA bands ranging from 250-4000 bp was obtained and 28 bands of which are polymorphic. The dendrogram formed 4 clusters. Cluster 1 consists of Bingin, Kelapa, Gulapasir, Nangka, Muani, Gonong, Penyalin, Gondok, Layu, Sudamala, Merah, Jaka, and Putih salak cultivars. Cluster 2 consists of Pada cultivar, cluster 3 consists of Injin cultivar, and cluster 4 consists of Nenas cultivar. This research is the first diversity analysis report on S. zalacca from Bali based on morphological and molecular characters.